Analisis Self-Confidence Siswa Kelas VIII Sekolah Menengah Pertama dalam Pembelajaran Matematika - Destiani, Irna Shersa (Program Studi Pendidikan Matematika, Universitas Majalengka, 2025)
The purpose of this study was to determine the self-confidence of junior high school students in learning mathematics. This study used a qualitative approach with descriptive methods with the subject of 35 students in class VIII of SMPN 2 West Karawang in the 2023/2024 academic year. Student self-confidence data is obtained from a non-test instrument in the form of a questionnaire which includes several indicators such as, believing in one's own abilities, acting independently in making decisions, having a positive self-concept, and daring to express opinions. The self-confidence scale questionnaire used in this study is a Likert scale model to measure answers based on statements submitted to respondents by giving a score to each answer item. The results showed that students in grade VIII of SMPN 2 West Karawang had a relatively good level of self-confidence in learning mathematics, with a percentage reaching 61%-80%.